Evaluating Intercorporate Risk, Returns, and Trends - Norgaard, Richard L. (Journal of Financial and Quantitative Analysis, 1971)
This article has described a technique for evaluating intercorporate performance using risk, return, and trend. By regressing risk and trend on return for a large number of companies, an average performance plane has been established. A company's performance is measured by determining its position relative to the plane.